(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The article is devoted to the implementation of personnel policy in municipalities. The influence of personnel policy on the effectiveness of management decisions is studied. Personnel policy in municipal structures plays an important role in determining the quality of administrative decisions of the administration. The effectiveness of management in the territory of the municipal formation depends on the chosen personnel policy and the competence of municipal employees who carry out the activities of the administration.